Integrating Expectation-Confirmation Theory and DeLone & McLean Model: Exploring the Impact of Website Quality on E-Satisfaction and E-Loyalty in the Sports Equipment and Apparel Industry - Anggara, Adi Wahyu (Faculty of Economics and Business | Universitas Diponegoro, 2025)
This study examines the complex interconnections of website quality, e-satisfaction, and e-loyalty in the evolving sports equipment and clothing sector. This research seeks to elucidate the aspects affecting online consumer behavior in this sector by merging Expectation-Confirmation Theory (ECT) with the DeLone and McLean IS Success Model (D&M IS Model). This study investigates how the dimensions of information, system, and service quality of a website influence consumer expectations, satisfaction, and loyalty, acknowledging the distinctive traits of the sports equipment and apparel industry, including the importance of brand reputation, customer engagement, and community development. Data were gathered from 196 online consumers using a meticulously crafted structured questionnaire and evaluated employing sophisticated structural equation modeling (SEM) techniques utilizing AMOS software. This study's findings provide strong empirical evidence for the substantial and beneficial influence of website quality on e-satisfaction, which subsequently serves as a vital catalyst for both attitudinal and behavioral loyalty among online consumers. The incorporation of ECT with the D&M IS model offers a more exhaustive theoretical framework for clarifying the psychological and behavioral mechanisms influencing consumer loyalty in the online environment.